Fabrication of ultra-stable boronic acid-functionalized quinoline-linked COF for selective adsorption of quercetin - Li, Wenhao; Zou, Ting; Wang, Ziyi; Zhang, Yuanyuan; Zhang, Juan (Analytica chimica acta, 2025)
Quercetin, a flavonoid with cis-diol moiety, is widely found in plants and exhibits significant pharmacological properties, including anti-inflammatory, antioxidant, and anti-tumor activities. Efficient adsorption and separation of quercetin from complex matrices are crucial for advancing health and nutrition research. However, the structural diversity of flavonoids poses challenges for their selective separation. Covalent organic frameworks (COFs) have emerged as promising adsorbents due to their high surface area and adsorption performance. However, most imine-linked COFs suffer from poor chemical stability under harsh conditions. There is a need for developing highly stable COFs with selective adsorption capabilities for quercetin and other cis-diol-containing compounds. A post-synthetic modification strategy was employed to convert COF-366 into a highly stable quinoline-linked boronic acid-functionalized COF (named COF-366-BA) via the aza-Diels-Alder reaction. COF-366-BA exhibited enhanced chemical and thermal stability, withstanding strong acidic and alkaline conditions. Characterization revealed a high specific surface area and excellent crystallinity. After functionalization with BA, COF-366-BA demonstrated superior selective adsorption performance for cis-diol-containing quercetin, adenosine, and naringin, with adsorption mechanisms involving boron affinity, π-π interactions, hydrogen bonding, and hydrophobic effects. Adsorption kinetics, isotherms, and thermodynamics were thoroughly investigated. A DSPE-HPLC method using COF-366-BA as an adsorbent was developed for the selective enrichment and detection of quercetin in black tea. Green metric evaluations including GAPI, Complex GAPI, AGREE, and AGREEprep confirmed the method's eco-friendliness. This work presents a significant advancement in the design of highly stable and functional COFs for selective adsorption cis-diol-containing compounds. COF-366-BA's robustness and selectivity make it a promising material for the enrichment and detection of cis-diols structural bioactive compounds in complex matrices. The green synthesis approach and practical application of quercetin detection in food and biological samples hold a significant importance in the health and nutrition fields. [Display omitted] •Boronic acid functionalized COF was fabricated via post-modification.•COF-366-BA exhibited good stability under harsh environments.•Adsorption involved boron affinity and multi-interactions, enabling selective quercetin capture.•GAPI, Complex GAPI, AGREE, and AGREEprep assessed method's environmental sustainability.•COF-366-BA-based DSPE-HPLC method enriched quercetin in black tea.